Peaceful School Counselors for School Violence in the Digital Era - Sobri, Ahmad Yusuf; Saputra, Nur Mega Aris; Abdullah, Dzulkifli (citeus, 2025)
The problem of violence that occurs in the world of education is a manifestation of the incomplete realization of schools as safe places. One strategy to make this happen is through the implementation of peace education in schools that involves all school members. School counselors are one of the key roles needed for the implementation of peace education in schools. This study aims to find out the role of school counselors in implementing peace education in schools. The study is a systematic literature review using the PRISMA stages. Fifteen academic articles were selected based on the main keywords: peace education in Indonesia, peace education, and peace education in guidance and counseling. The articles obtained became the basis for the author in formulating how the role of school counselors in implementing peace education to prevent violence in schools. The results described the role of school counselors in peace education in schools as a strategic role including planning, implementing, and evaluating. School counselors should implement guidance services to develop character and provide counseling services to realize peace education in schools. The role of school counselors will contribute to how peace education is implemented in preventing violence in schools.